“Feeling in Control”: Optimal Busyness and the Temporality of Organizational Controls - Lupu, Ioana; Rokka, Joonas (Organization Science, 2022)
This study extends prior research seeking to understand the reproduction and persistence of excessive busyness in professional settings by addressing the relationship between organizational controls and temporal experiences. Drawing on 146 interviews and more than 300 weekly diaries in two professional service firms, we develop a framework centered on the emerging concept of optimal busyness, an attractive, short-lived temporal experience that people try to reproduce/prolong because it makes them feel energized and productive as well as in control of their time. Our findings show that individuals continuously navigate between different temporal experiences separated by a fine line, quiet time, optimal busyness, and excessive busyness, and that optimal busyness that they strive for is a fragile and fleeting state difficult to achieve and maintain. We show that these temporal experiences are the effect of the temporality of controls—that is, the ability of controls to shape professionals’ temporal experience through structuring, rarefying, and synchronizing temporality. Moreover, we find that professionals who regularly face high temporal pressures seek to cope with these by attempting to construct/prolong optimal busyness through manipulating the pace, focus, and length of their temporal experiences, a process we call control of temporality. Our study contributes to a better understanding of the reproduction of busyness by explaining why professionals in their attempts to feel in control of their time routinely end up overworking.